2006
DOI: 10.1111/j.1440-1797.2006.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between depressive affect and malnutrition‐inflammation complex syndrome in haemodialysis patients

Abstract: The results suggest that MIS and MSPSS are the strongest predictors of depressive affect in HD patients. Further research is needed to understand the causal relationship between depressive affect and MICS in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 15 publications
1
18
1
3
Order By: Relevance
“…Several recent reports have demonstrated a possible link between malnutrition, inflammation and atherosclerosis with depressive symptoms in patients with chronic kidney disease [14,15], and severity of depression was correlated with malnutrition and inflammatory scores in hemodialysis patients [33], which may also be applied to peritoneal dialysis patients. In this study, we showed that a depressive symptom in CAPD patients was strongly related to poor nutritional status and chronic inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reports have demonstrated a possible link between malnutrition, inflammation and atherosclerosis with depressive symptoms in patients with chronic kidney disease [14,15], and severity of depression was correlated with malnutrition and inflammatory scores in hemodialysis patients [33], which may also be applied to peritoneal dialysis patients. In this study, we showed that a depressive symptom in CAPD patients was strongly related to poor nutritional status and chronic inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, depression is known to increase the incidence and worsen the outcome of cardiovascular diseases [13], and a correlation between depression, malnutrition and inflammation has been reported in patients with chronic kidney disease [14,15,16]. Considering the fact that inflammation is an important mediator for cardiovascular disease, there is a possibility that depression might contribute to increased cardiovascular mortality and morbidity in ESRD patients [17,18] by aggravating malnutrition-inflammation-atherosclerosis (MIA) interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The BDI is documented as a valid index of depression and BDI scores correlate well with the diagnostic criteria for depression. The advantage of the BDI is that it places the subject within a range of depression severity, rather than merely identifying whether the person meets certain diagnostic criteria [8]. It has been used frequently to measure severity of depressive symptoms in HD patients and is a useful screen for managing clinical depression in this patient group [9].…”
Section: Beck Depression Inventorymentioning
confidence: 99%
“…Several studies have shown that MIS is superior to conventional SGA and to individual laboratory values as a predictor of dialysis outcome [25][26][27][28]. We used the MIS tool to assess the extent of MICS and found a significant positive correlation between HAMD score and MIS among the dialysis patients, as reported previously by Micozkadioglu et al [29] in patients on hemodialysis, which was the first investigation to examine the relationship between depression and MICS.…”
Section: Discussionmentioning
confidence: 55%